CODESRIA Bulletin, No 6, 2021: Special Issue Reflections on Social Policy in Africa - Journal System (CODESRIA Bulletin, 2021)
In this issue Editorial Godwin R. Murunga & Ibrahim O. Ogachi ............................... 1 Éditorial Godwin R. Murunga & Ibrahim O. Ogachi ........................ 4 Reflections on Social Policy in the African Context : An Introduction Jimi Adesina ................................................................... 7 1. Rethinking Social Policy in Africa—a Transformative Approach Katja Hujo ...............................................................11 2. Gender, Poverty and Land in Africa : A Transformative Social Policy Perspective Newman Tekwa.....................................................17 3. Land Reform as Social Policy : Exploring the Redistribution and Social Protection Outcomes in Goromonzi District, Zimbabwe Clement Chipenda.......................................................21 4. The Male Breadwinner Myth : The South African Case Marlize Rabe.......................................................27 5. Social Health Insurance in Nigeria : Rethinking the Approach for Effective Health Care Delivery Omoruan Augustine Idowu....................................31 6. Excavating communal mutual support praxis in two townships in South Africa : preliminary notes for social policy learning Kolawole Omomowo & Jimi Adesina.......................36